Implementasi Standard Operasional Procedure (SOP) Receiving Section di the Zuri Hotel Pekanbaru - Rufi ‘Aisyah; Pasaribu Pasaribu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the implementation of Standard Operating Procedures (SOP) in the receiving section at The Zuri Hotel Pekanbaru. Using a qualitative descriptive method with purposive sampling to select informants, data were collected through interviews, observations, and documentation. The collected data were transcribed and analyzed using Nvivo software. The findings reveal that the receiving section has implemented SOP related to the receipt, storage, and distribution of goods in accordance with hotel standards. However, several procedures were found to be inadequately executed, indicating gaps between the SOP guidelines and actual practice.